(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Many people know about diabetes mellitus, one of the diseases that shortens a person’s life, but not everyone has information about non-diabetic diabetes, which is no less dangerous for health. In diabetes insipidus, the body does not respond to an important hormone involved in metabolism, as in diabetes. In diabetes insipidus, the body does not produce the hormone vasopressin, which responds to the release of urine, or there is a problem with it. This article provides information about the drugs used in the treatment of diabetes insipidus.